Collagen Drink Entrepreneurship Training and Mentoring - Wibowo, Teguh Setiawan; Negara, Sri Bintang Sahara Mahaputra Kusuma (PT FORMOSA CENDEKIA GLOBAL, 2024)
The goal is to maintain beauty as desired by most women, especially middle-aged and elderly women and prevent diseases associated with collagen deficiency in the body. The method used is presentation, question and answer/discussion and mentoring (in the form of practice and evaluation) with preparation carried out for 2 months and mentoring carried out for 4 months. The result was that community service activities through training and assistance in making collagen drinks received enthusiasm and quite a good response from a total of 148 participants who attended the Universitas Muhammadiyah Lamongan auditorium and entered the room on the Zoom’s webinar. It is hoped that the Small and Medium Enterprise (SMEs) on the Universitas Muhammadiyah Lamongan can use this activity as a start to making collagen drink products from herbal ingredients and marine sources that are in demand by young people and the environment around the campus. Apart from that, it can be sold freely as a substitute for collagen drinks made from synthetic or chemical ingredients. Then, the general public who participates is expected to be able to make collagen drinks independently at home.